Lifetime prediction for electrical drives – limiting factor capacity - Neuburger, Martin; Lehner, Wolf-Dieter; Neuberger, Nikolaus (НТУ "ХПІ", 2013)
The paper deals with approaches for estimation of capacitors’ condition and performances in context of their lifetime prediction for electrical drives applications. The physical structure and equivalent circuit of the high-voltage capacitor is given. Experiments for evaluation of these parameters are described. Dependences of capacitors’ technical condition and the estimated parameters are given.

В статті розглянуті підходи визначення технічного стану і параметрів конденсаторів в контексті прогнозування їх терміну експлуатації в складі електричних приводів. Наданий опис фізичної структури високовольтного конденсатора та пояснена його схема заміщення. Наведений опис експериментів щодо визначення параметрів схеми заміщення. Показані залежності показників технічного стану від експериментально визначених параметрів.